Peningkatan Pemahaman Legalitas Usaha Bagi Pelaku Usaha Kecil Menengah Pada Masyarakat Desa Mergosari Kabupaten Wonosobo - Ningsih, Ayup Suran; Fidiyani, Rini; Rasdi, Rasdi; Ramli, Asmarani; Muhtada, Dani; Hanum, Holy Latifah; Khomariyah, Maulida Nurul; Putri, Fadilla Elza Aida; Wardhani, Harumsari Puspa (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
Micro, Small, and Medium Enterprises are business activities that can expand employment and provide extensive economic services to the community. They can also play a role in equalizing and increasing public income, promoting economic growth, and contributing to national stability. In addition, Micro, Small, and Medium Enterprises are one of the main pillars of the national economy that must get the most opportunities, support, protection, and development as a form of firm partiality to the people's economic business groups, without neglecting the role of Large Enterprises and State-Owned Enterprises. In Law No. 11 of 2020 concerning Job Creation, simplification of Business Permissions through Integrated Online Licensing (Online Single Submission). Mergosari Village became the first to produce batik with a typical Wonosobo motif through the Batik Mergosari community named Batik Carica Lestari. The problems partners face include the lack of knowledge and understanding of small- and medium-sized business actors in Mergosari Village regarding the legal aspects of business actors, which still need to be improved. The solution to this problem is to provide education using lectures and seminars with village officials and small and medium enterprises of Mergosari Village, and small and medium enterprises should have a Business Master Number (NIB). The method of service is to provide education through socialization and mentoring practices.